1997
DOI: 10.1093/bja/78.1.88
|View full text |Cite
|
Sign up to set email alerts
|

Spinal anaesthesia inhibits central temporal summation

Abstract: SummaryIn a previous investigation we found that extradural anaesthesia did not adequately inhibit temporal summation of repeated electrical stimuli: pain to repeated stimuli was blocked in only one of 10 patients, and pain thresholds to repeated stimuli were significantly lower than pain thresholds to a single stimulus. In this study we have investigated in 10 patients the effect of spinal anaesthesia on temporal summation, assessed by repeated electrical stimulation of the sural nerve. Plain 0.5% bupivacaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 6 publications
1
23
0
5
Order By: Relevance
“…pinprick, cold) may be blocked, but spinal cord mechanisms may result in repeated stimuli (temporal summation) or stimuli from adjacent regions (spatial summation), evoking pain and revealing a 'failed block'. Intrathecal block is better than epidural at inhibiting spatial summation, 31 and this partly explains the more profound block produced. In addition, demonstration of the segmental extent of block of one modality does not enable accurate prediction of any other.…”
Section: Assessment Of Intrathecal Drug Spreadmentioning
confidence: 99%
“…pinprick, cold) may be blocked, but spinal cord mechanisms may result in repeated stimuli (temporal summation) or stimuli from adjacent regions (spatial summation), evoking pain and revealing a 'failed block'. Intrathecal block is better than epidural at inhibiting spatial summation, 31 and this partly explains the more profound block produced. In addition, demonstration of the segmental extent of block of one modality does not enable accurate prediction of any other.…”
Section: Assessment Of Intrathecal Drug Spreadmentioning
confidence: 99%
“…Different sites of action of local anaesthetics (and opiates) with differences in blocking central sensitization may contribute to a preemptive effect. In a clinical model, it was shown that spinal anaesthesia was able to suppress temporal summation, whereas EDA had only partial effects [10,11]; however, results of clinical studies regarding the value of preemptive analgesia are controversial [12].…”
Section: Introductionmentioning
confidence: 99%
“…13 Our results suggest that epidural anesthesia with alkalinized 2% lidocaine and epinephrine may inhibit temporal summation also. Protection of sensory neurons against central sensitization may offer FIGURE 1 Changes in pain threshold (A, B).…”
Section: Me Et Th Ho Od Ds Smentioning
confidence: 58%